Analyzing Flexible Learning Implementation using Decision Tree Approach - Frederick Flores Patacsil; Palanyos Dina; Bobby Roaring (Universitas Negeri Makassar, 2023)
Philippine Commission of Higher Higher Education (CHED) compelled Higher Education Institutions (HEIs) to adopt flexible teaching and learning and urged them to employ available flexible curriculum with incorporates both synchronous and asynchronous learning modes and a mixture of teaching and learning methods. This study aims to analyzed the implementation of flexible learning using decision trees. The research utilized descriptive research, where a descriptive survey was designed to identify the problems encountered, problems/ challenges, and suggest solutions by university students in the implementation of flexible learning in the campus. Problems/challenges on no/unreliable internet connection and cost of internet connectivity are the two (2) major problems that were encountered by the students in the implementation of flexible learning in the university. Administrators should coordinate with the local government units to assist students in terms of internet connections. PSU should provide subsidies to assist students with the needed devices for flexible learning.